Development plan for the period 1970 to 1974 - Kenya ([Nairobi?], 1969)
This plan (kenya$1 (Bs second) covers the projected growth of the economy over the five calendar years 1970-74 and, more specifically, the investment programme of the government in the five financial years 1969/70 to 1973/74. s
lje 17/10/18
Loans
Keywords: Economic policy; Kenya; Kenya